Optical burst switching in dynamic VPN lightpath setup - Teoh, Yee Chuin. (2008)
The concept of wavelength division multiplexing (WDM) has been implemented widely in optical networks in order to provide us an opportunity to multiply the network capacity. Recently, Virutal Private Network (VPN) has appeared to be a simple, flexible, robust and scalable mechanism that provides traffic security in an organization, over a shared public infrastructure such as the Internet. (Asst. Prof. Qin Yang)